Inflammatory Monocyte Subsets Correlation with Iron Levels in Low Vitamin D Pediatric Transfusion-Dependent Thalassemia - Ghozali M; Matahari M; Cahyadi AI; Agustini SD; Ghrahani R; Reniarti L; Setiabudiawan B; Panigoro R (Journal of Inflammation Research)
Mohammad Ghozali,1 Matahari Matahari,2 Adi Imam Cahyadi,1 Sri Devi Agustini,2 Reni Ghrahani,3 Lelani Reniarti,3 Budi Setiabudiawan,3 Ramdan Panigoro1 1Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, 45363, Indonesia; 2Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, 45363, Indonesia; 3Department of Pediatrics, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, 40161, IndonesiaCorrespondence: Mohammad Ghozali, Email moh.ghozali@unpad.ac.idBackground: Patients with transfusion-dependent thalassemia experience iron dysregulation, which affects the immune response. Surface proteins such as FcγRIII (CD16), lipopolysaccharide receptor (CD14), and human leukocyte antigen (HLA-DR) on monocytes are crucial for innate and adaptive responses. Blood monocytes, identified by their CD14 and CD16 expression, show functional diversity during injury or inflammation. Considering the mechanisms of vitamin D activation and its potential interaction with monocytes, further investigation of its immunomodulatory role in transfusion-dependent thalassemia is essential.Purpose: This study evaluated monocyte subsets, population, and surface receptor expression (CD14, CD16, and HLA-DR), and their association with iron status and vitamin D levels in patients with transfusion-dependent thalassemia.Patients and Methods: Fifty lysed erythrocyte-heparinized whole blood samples from transfusion-dependent thalassemia patients were analyzed by flow cytometry and classified into three monocyte subsets: CD14++CD16- (classical), CD14++CD16+ (intermediate), and CD14+CD16++ (non-classical). Cell percentage referred to the monocyte subset population. Median fluorescence intensity (MFI) indicated surface protein expression. The 25(OH)vitamin D level was used to measure vitamin D levels. Iron status was assessed using ferritin and serum iron levels. A correlational study was performed.Results: We did not find a correlation between low vitamin D levels (22.9 ng/mL ± 3.9) and monocyte characteristics, iron status, or hematology profile. However, we observed a negative correlation between the percentage of intermediate and non-classical monocytes and hemoglobin and ferritin levels (P = 0.02, r = − 0.3; P = 0.04, r = − 0.3). Additionally, we found a positive correlation between the median fluorescence intensity (MFI) of CD14 in non-classical monocytes and serum iron (P = 0.04, r = 0.3).Conclusion: Our findings suggest that iron overload and anemia may influence the function of inflammatory monocyte subsets. Considering the immunomodulatory role of vitamin D through monocyte modulation during pathogen insult, further research utilizing a whole-blood stimulation assay is imperative.Keywords: ferritin, hemoglobin, iron, monocyte, thalassemia, vitamin D